Assessment of the application for renewal of authorisation of AviPlus® as a feed additive for all porcine species (weaned), chickens for fattening, chickens reared for laying, minor poultry species for fattening, minor poultry species reared for laying. (16th April 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: AviPlus ® is an additive containing a mixture of sorbic acid, citric acid, thymol and vanillin. The applicant requested for the renewal of the authorisation for AviPlus ® when used as a feed additive in all porcine species (weaned), chickens for fattening, chickens reared for laying, minor poultry species for fattening, minor poultry species reared for laying. The applicant has provided evidence that the additive in the market complies with the conditions of the authorisation. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel) confirms that the use of AviPlus ® under the current authorized conditions of use is safe for the target species, the consumers, the users and the environment. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.